Legal Analysis of Judgment No. 131/Pid.Sus-Lh/2025/Pn.Mjy on the Criminal Case of Possession of a Javan Porcupine from the Perspective of Ecological Justice - Perdana, Hendra Putra (Jurnal Indonesia Sosial Sains, 2026)
This research is motivated by the increasing threat to biodiversity in Indonesia, particularly due to the illegal possession of protected wildlife, which reflects gaps in law enforcement and weak integration of ecological values in judicial decisions. Indonesia, as a mega-biodiversity country, faces serious challenges in ensuring effective protection of endangered species through its legal system. This research aims to analyze the judge's considerations in imposing criminal penalties on the perpetrators of the ownership of protected animals of the Javan Hedgehog (Hystrix javanica) in Decision Number 131/Pid.Sus-LH/2025/PN.Mjy. Using normative juridical methods with a case study approach and an ecological justice perspective, this study dissects the ratio decidendi of judges in applying criminal sanctions. The results of the study showed that the Panel of Judges legally proved the Defendant's violation of Article 21 paragraph (2) of Law No. 5 of 1990. However, the imposition of a 5-month prison sentence with a probation period of 1 year and a minimum fine reflects an anthropocentric paradigm that prioritizes the social background of the defendant over ecosystem losses. The implication is that this ruling risks weakening the deterrent effect and protection of biodiversity in Indonesia. Progressive law enforcement based on ecological justice is needed so that judges' verdicts are not only procedural, but also able to ensure the sustainable restoration of environmental functions.